Technology readiness and users satisfaction towards self-service technology at Malaysian Airport - Nik Abdullah, Nik Ab. Halim (IFRD, 2012)

(untitled)
This study examines the relationship between four dimensions of Technology Readiness Index (TR) namely optimism, innovativeness, insecurity, discomfort, and the level of customer’s satisfaction towards the use of self-service technology (SSTs) at the airport.SSTs used by the airport operators or airlines at the terminal for check-in or when performing other transactions includes booking airline ticket online, kiosk check-in and mobile check-in.At the same time, this study also tries to look at whether there is any difference in technology readiness between different demographic groups of Malaysians.Survey questionnaires were distributed to passengers at Kuala Lumpur International Airport (KLIA) and Low Cost Carrier Terminal (LCCT) in Sepang, Selangor, Malaysia.The result of the analysis shows that innovativeness and optimism have a positive relationship with customer satisfaction.There are also differences in technology readiness among different gender for innovativeness and insecurity index.The implication of the study suggests that Malaysia’s airport or airline providers should increase customer satisfaction especially by introducing new innovative technology at their premises.The findings may also help firms develop their strategy to further increase the customer’s satisfaction when using the self-service technology (SST) at airports in Malaysia.